Characterisation of Maclura cochinchinensis (Lour.) Corner Trunk Heartwood Extract and its Toxicity Evaluation - Esti Mumpuni; Dwi Yuni Kurniawati; Ratna Djamil; Diah Kartika Pratami (IIUM Press, International Islamic University Malaysia, 2024)
Introduction:  Maclura cochinchinensis is widely used as a natural dye for clothing in Indonesia. Besides, there are some researches about its activities as an antioxidant, antimicrobial, and antidiabetic. However, there is a lack of comprehensive information regarding the standard characteristics and safety of use of its heartwood extract. Therefore, this study aimed to characterize M. cochinchinensis heartwood extract and to evaluate its toxicity.  Method:  To obtain the extract, coarse powder of M. cochinchinensis heartwood was macerated using 70% ethanol and evaporated by vacuum rotavapor. Subsequently, phytochemical screening and thin-layer chromatography profiling were carried out, while the toxicity evaluation was conducted using brine shrimp lethality test. Results: The phytochemical screening showed that this extract contained flavonoids, saponins, tannins, steroids, triterpenoids, coumarins, and essential oils. The extract exhibited a dark brown colour, distinct odour, flavourlessness, the value of water-soluble content, ethanol-soluble extract content, loss on drying, moisture content, moisture content, total ash content, acid-insoluble ash content, and water-soluble ash content of 31.44%±1.31, 50.44%±8.48, 9.51%±0.32, 1.62%±0.48, 4.93%±0.27, 1.10%±0.11, 3.81%±0.19, respectively. The residual solvent and heavy metal contamination were undetectable. Microbial contamination was minimal and dominated by a semipolar compound, and brine shrimp assay indicated low toxicity with an LC50 value of 174.40 mg/L. Conclusion:  M. cochinchinensis heartwood extract has good quality and tends to be safe for the environment. This research obtained data that could be used as a supporting evidence for more specific utilization of M. cochinchinensis heartwood and its isolated compounds.